2004
DOI: 10.1017/s104795110400304x
|View full text |Cite
|
Sign up to set email alerts
|

The prenatal diagnosis of, and short-term outcome for, patients with congenitally corrected transposition

Abstract: Congenitally corrected transposition is a rare congenital anomaly, with only a few cases diagnosed and reported prenatally even in the largest fetal series. To determine the morphologic features and outcome for the lesion as recognized during fetal life, we reviewed the fetal and postnatal echocardiograms and medical records of 11 consecutive cases of congenitally corrected transposition. These were identified among 230 (4.7%) consecutive cases of structural cardiac disease referred to our fetal cardiology uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 24 publications
0
3
0
2
Order By: Relevance
“…We had four cases with anomalies in the renal and urinary system, three cases of anomalies in the gastrointestinal tract, one case with central nervous system anomaly and one case with Ivemark syndrome. Prenatal karyotyping of the fetus was available in 30/54 (55.6 %) cases with confirmed chromosomal anomalies in ▪ DORV 1/7 (14) ▪ atrioventricular block 1/7 (14) ASD, RAA, left persistent superior vena cava 1/7 (14) unknown 1/7 (14) 4/30 (13.3 %). In two patients a microdeletion 22q11 was found, one fetus had a duplication of chromosome 5 and there was one chromosomal inversion (inv(7)(q34q36)).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We had four cases with anomalies in the renal and urinary system, three cases of anomalies in the gastrointestinal tract, one case with central nervous system anomaly and one case with Ivemark syndrome. Prenatal karyotyping of the fetus was available in 30/54 (55.6 %) cases with confirmed chromosomal anomalies in ▪ DORV 1/7 (14) ▪ atrioventricular block 1/7 (14) ASD, RAA, left persistent superior vena cava 1/7 (14) unknown 1/7 (14) 4/30 (13.3 %). In two patients a microdeletion 22q11 was found, one fetus had a duplication of chromosome 5 and there was one chromosomal inversion (inv(7)(q34q36)).…”
Section: Resultsmentioning
confidence: 99%
“…Although most neonates are clinically stable at birth, the long-term outcome of this cardiac anomaly is dependent on the myocardial function of the morphologic right ventricle, tricuspid valve regurgitation and the development of congenital heart block [7][8][9][10][11][12]. Due to the rarity of this pathology, outcome data on prenatally diagnosed ccTGA is scarce and is based mainly on case series or studies with small numbers of patients [5,[13][14][15][16][17]. The aim of our study was firstly to investigate the natural history and associated anomalies and secondly to analyze the outcome of patients in prenatally diagnosed ccTGA.…”
Section: Introductionmentioning
confidence: 99%
“…However, in some cases, tricuspid or pulmonary valve regurgitation was too mild to be detected, or difficult to detect due to the position of the fetus. 15 Determination of the ratio of pulmonary artery blood flow AT and ET is a novel approach for monitoring pulmonary artery pressure. The results of this study indicated that AT was negatively correlated with PASP, and that increased PASP could lead to a decrease in AT.…”
Section: Discussionmentioning
confidence: 99%
“…Les deux anomalies peuvent en effet coexister dans la même famille, en particulier en cas de consanguinité. La présentation du pronostic doit cependant rester réservée [342]. Lors du diagnostic, deux situations doivent être envisagées : 1. la TGVc n'est pas isolée ou s'accompagne déjà de manifestations de mauvaise tolérance.…”
Section: Conseil Aux Parentsunclassified
“…Dans les grossesses gémellaires, un foetus peut être atteint et l'autre non [341]. Si cette phase se déroule sans incident, l'enfant reste menacé par l'apparition inopinée d'un trouble conductif nécessitant l'implantation d'un pacemaker ou, plus rarement, de troubles du rythme [337,342]. Le pronostic est alors très péjoratif, avec un risque élevé de MFIU en cas de trouble conductif ou de décès dans les premiers mois de vie en cas d'insuffisance tricuspide, avec peu de possibilités chirurgicales ; 2. la TGVc apparaît isolée lors du diagnostic, avec une tricuspide bien continente.…”
Section: Conseil Aux Parentsunclassified